Cost-effectiveness of adjuvant atezolizumab versus best supportive care in the treatment of patients with resectable early-stage non-small cell lung cancer and overexpression of PD-L1. (31st December 2023) - Escudero-Vilaplana, Vicente; Collado-Borrell, Roberto; De Castro, Javier; Insa, Amelia; Martínez, Alex; Fernández, Elena; Sullivan, Ivana; Flores, Andrés; Arrabal, Natalia; Carcedo, David; Manzaneque, Alba
Abstract: Aims: To assess the cost-effectiveness of adjuvant atezolizumab in the treatment of early-stage NSCLC patients (stage II–IIIA) with expression PD-L1 ≥ 50% without mutations in EGFR or ALK rearrangements in Spain. Materials and methods: A 5-states Markov model (DFS, locoregional recurrence, 1 L-metastatic recurrence, 2 L-metastatic recurrence, and death states) was adapted to the Spanish setting. Demographic characteristics of the hypothetical cohort, transition probabilities from the DFS state, and safety parameters were obtained from IMpower010 study (GO29527). Transition probabilities from locoregional and metastatic health states were obtained from the literature. The usual clinical practice in Spain (use of health resources, management of the disease, etc.) was obtained from a previous analysis carried out by the authors of this study. A societal perspective was considered so both direct and indirect costs were included (expressed in € of 2021). A lifetime horizon was used, so costs and health outcomes were discounted at 3% per year. Sensitivity analyses were performed to evaluate uncertainty. Results: Over a lifetime horizon, treatment with adjuvant atezolizumab provided greater effectiveness (+2.61 life years [LY] and +1.95 quality-adjusted life years [QALY]) and higher cost (€+22, 538) than BSC. The incremental cost-effectiveness ratio (ICER) and incremental cost-utility ratios (ICUR) of the analysis were €8, 625/LY gained and €11, 583/QALY gained, respectively. Robustness of these base-case results was confirmed by the sensitivity analyses performed. In the probabilistic sensitivity analysis, 90% of the simulations performed showed that adjuvant atezolizumab is cost-effective versus BSC, considering a threshold of €30, 000/QALY. Conclusions: Our results showed that adjuvant treatment with atezolizumab in patients with early-stage resected NSCLC with overexpression of PD-L1 and without EGFR and ALK mutations is cost-effective versus BSC as the ICERs and ICURs obtained are below the cost-effectiveness thresholds commonly considered in Spain, thus offering a new treatment alternative for these patients.